2015
DOI: 10.1590/s0100-736x2015001000003
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Rhodococcus equi and putative association with macrolide resistance

Abstract: RESUMO.-[Formação de biofilme por Rhodococcus equi e posspivel associação com resistência a macrolídeos.]Rhodococcus equi é um patógeno intracelular facultativo, o qual causa pneumonia piogranulosa severa em potros e lesões semelhantes à tuberculose em humanos. A sua capacidade de formar biofilme foi descrita em cepas humanas, isoladas a partir de doenças crônicas associadas a falhas de tratamento. Este estudo teve como objetivo verificar a formação de biofilme por 113 cepas de R. equi, isoladas a partir de am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…However, a statistically significant reduction of R. equi sessile aggregates emerged from our data, particularly when treated with AZM and AZM/RIF 2:1 over a prolonged period of time. These results are in good agreement with a previous study [20] which, however, employed different methodological approaches. On the other hand, the role of RIF against R. equi biofilm is controversial.…”
Section: Macrolides and Rifampicin Versus Biofilm: A Controversial Issuesupporting
confidence: 93%
See 2 more Smart Citations
“…However, a statistically significant reduction of R. equi sessile aggregates emerged from our data, particularly when treated with AZM and AZM/RIF 2:1 over a prolonged period of time. These results are in good agreement with a previous study [20] which, however, employed different methodological approaches. On the other hand, the role of RIF against R. equi biofilm is controversial.…”
Section: Macrolides and Rifampicin Versus Biofilm: A Controversial Issuesupporting
confidence: 93%
“…To date, poor literature reporting the capacity of R. equi to aggregate in a self-produced matrix has been available. R. equi seems to be able to produce biofilms, although some clinical isolates have been found to be non-biofilm producers at 24 h of incubation [20]. The kinetic crystal violet assay performed in this work demonstrated that 100% (40/40) of the rhodococci evaluated were biofilm producers with a suggested biofilm production time of at least 48 h, while incubation for longer than 72 h allowed more abundant biofilm development.…”
Section: In Vitro Model Of Rhodococcus Equi Biofilm Growthmentioning
confidence: 65%
See 1 more Smart Citation
“…Recently, our research group demonstrated the formation of biofilms by Rhodococcus equi from clinical and non‐clinical samples of horses (Gressler et al . ). In addition, Peixoto et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Gressler et al . ). However, studies involving biofilms in the micro‐organisms of veterinary interest are still scarce, including Moraxella genus.…”
Section: Introductionmentioning
confidence: 97%